ANALYSIS OF FACTORS THAT AFFECT THE CAPITAL STRUCTURE AND VALUE OF MANUFACTURING FIRMS IN INDONESIA - Christian Siauwijaya (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
Purpose of this study is to analyze the factors that affect capital structure and value of firm. In this research, the dependent variable used is value of firm, which is also influenced by capital structure as an intervening variable. Influence between variables was analyzed using multiple linear analysis in pooled data formation. Based on the hypothesis testing result, it’s found that managerial ownership has a significant effect on capital structure, but isn’t significant to the value of firm. Institutional ownership significantly affects the value of firm but does not affect the capital structure. Profitability has a significant effect on capital structure and value of firm. The asset structure has a significant effect on the value of firm, but not significant on the capital structure. Capital expenditure has a significant effect on capital structure, but not significant on value of firm. Sales growth has no significant effect on capital structure and value of firm. Corporate social responsibility has a significant effect on the value of firm but does not affect the capital structure. Firm size has a significant effect on capital structure and value of firm. Growth opportunity has a significant effect on capital structure and value of firm. Capital structure has a significant effect on value of firm.